2013
DOI: 10.1007/s13311-013-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and ncRNAs in Brain Function and Disease: Mechanisms and Prospects for Therapy

Abstract: The most fundamental roles of non-coding RNAs (ncRNAs) and epigenetic mechanisms are the guidance of cellular differentiation in development and the regulation of gene expression in adult tissues. In brain, both ncRNAs and the various epigenetic gene regulatory mechanisms play a fundamental role in neurogenesis and normal neuronal function. Thus, epigenetic chromatin remodelling can render coding sites transcriptionally inactive by DNA methylation, histone modifications or antisense RNA interactions. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 140 publications
1
34
0
Order By: Relevance
“…41 These data suggest that epigenetics plays a dynamic role in the relationship between HPA axis dysregulation and psychopathology even outside of a developmental sensitive period. Given the need for epigenetic mechanisms in normal brain functioning, 42 we…”
mentioning
confidence: 99%
“…41 These data suggest that epigenetics plays a dynamic role in the relationship between HPA axis dysregulation and psychopathology even outside of a developmental sensitive period. Given the need for epigenetic mechanisms in normal brain functioning, 42 we…”
mentioning
confidence: 99%
“…Recent studies showed that miR-329 is upregulated in the brain of a mouse model of Rett syndrome; these mice have mutations in the MeCP2 gene, and the MeCP2 level is elevated in neoplastic breast tissues. [27][28][29] To test the possibility that MeCP2 is responsible for the downregulation of miR-329 in breast cancer, we assessed miR-329 expression after transfection of Mecp2 siRNA into MCF7 cells. As shown in Figure 6d, downregulation of MeCP2 resulted in upregulation of miR-329.…”
mentioning
confidence: 99%
“…Experimental evidence has shown that the mammalian transcriptome includes a number of noncoding RNAs (ncRNAs), such as short-noncoding RNAs (sncRNAs), microRNAs (miRNAs), long-noncoding RNAs (lncRNAs), which have been implicated in epigenetic silencing of specific genes [48,49]. Recent data demonstrate that ncRNAs are abundantly transcribed from the human genome, enriched in the brain, and have fundamental regulatory functions in neurogenesis and brain function [50].…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%